Digital imaging and prehistoric imagery: a new analysis of the Folkton Drums. (October 2015) - Jones, Andrew Meirion; Cochrane, Andrew; Carter, Chris; Dawson, Ian; Díaz-Guardamino, Marta; Kotoula, Eleni; Minkin, Louisa
Abstract: Abstract : The Folkton 'Drums' constitute three of the most remarkable decorated objects from Neolithic Britain. New analysis using Reflectance Transformation Imaging and photogrammetry has revealed evidence for previously unrecorded motifs, erasure and reworking. Hence these chalk drums were not decorated according to a single, pre-ordained scheme, but were successively carved and recarved over time. Such practices may have been widespread in the making of artefacts in Neolithic Britain. The study of these drums also demonstrates the ability of these new techniques not only to record visible motifs, but to document erased and reworked motifs clearly.